Incidence and clinical features of endoscopic ulcers developing after gastrectomy - Chung, Woo Chul (Baishideng Publishing Group Co., Limited, 2012)
AIM: To determine the precise incidence and clinical features of endoscopic ulcers following gastrectomy. METHODS: A consecutive series of patients who underwent endoscopic examination following gastrectomy between 2005 and 2010 was retrospectively analyzed. A total of 78 patients with endoscopic ulcers and 759 without ulcers following gastrectomy were enrolled. We analyzed differences in patient age, sex, size of the lesions, method of operation, indications for gastric resection, and infection rates of Helicobacter pylori (H. pylori) between the nonulcer and ulcer groups. RESULTS: The incidence of endoscopic ulcers after gastrectomy was 9.3% and that of marginal ulcers was 8.6%. Ulcers were more common in patients with Billroth II anastomosis and pre-existing conditions for peptic ulcer disease (PUD). Infection rates of H. pyloridid not differ significantly between the two groups. The patients who underwent operations to treat PUD had lower initial levels of hemoglobin and higher rates of hospital admission. CONCLUSION: H. pylori was not an important factor in ulcerogenesis following gastrectomy. For patients who underwent surgery for PUD, clinical course of marginal ulcers was more severe.